Physical and Mechanical Analysis of Two Layers of Cotton Silk in Knitted Tissues (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the work under study, the influence of indicators of the numerical values of the linear densities of cotton and silk yarn and the percentage in the structure of cotton, silk, two-layer knitwear for physical and mechanical properties.